Continuous glucose monitoring of a runner during five marathons - Oishi, A.; Makita, N.; Kishi, S.; Isogawa, A.; Iiri, T. (Science & Sports, 2018)
Introduction: Now in the global running boom, many people enjoy full-marathon, from top athletes to city runners. To understand glucose fluctuations during full-marathon would be useful to discuss the running performance and exercise intensity. There is a report concerning the continuous glucose monitoring (CGM) of three runners with type 1 diabetes during full-marathon, and that of two elite runners during 100km running race. However, there are little CGM data of healthy subjects during full-marathon as far as we know. The purpose of this study is to observe glucose fluctuation during full-marathon by CGM with running performance and exercise intensity. Summary of facts and results: CGM was performed five times during full-marathon of one same healthy runner and the heart rate and running speed were monitored. Five CGM data during full-marathon were obtained. Three of them showed the flat pattern. One of the left two showed the ascending pattern, in which the glucose level went up to more than 140mg/dL. The other one showed the descending pattern. The best running performance was observed in the flat pattern. Conclusion: CGM is a useful tool for monitoring glucose fluctuation during long distance running. These data would be helpful as a pilot study to understand glucose metabolism and performance during endurance exercises.